2011
DOI: 10.1111/j.1460-9568.2011.07745.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of medial temporal and posteromedial cortices in early Alzheimer’s disease

Abstract: Medial temporal lobe (MTL) atrophy and posteromedial cortical hypometabolism are consistent imaging findings in Alzheimer's disease (AD). As the MTL memory structures are affected early in the course of AD by neurofibrillary tangle pathology, the posteromedial metabolic abnormalities have been postulated to represent remote effects of MTL alterations. In this study, we investigated with functional MRI (fMRI) the structure-function relationship between the MTL and posteromedial regions, including the retrosplen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 103 publications
(245 reference statements)
0
16
1
Order By: Relevance
“…It has been found that AD patients have reduced activity in the MTL [117], particularly in the hippocampus [117][118][119][120][121], but also in the entorhinal cortex [117], while an increased activation has been reported in the prefrontal cortex, probably, due to a compensation mechanism [122,123]. Deactivation in posteromedial cortical areas such as the posterior cingulate and the medial parietal cortex has also been found to be anomalous in AD patients [124,125]. Nevertheless, these anomalies are much less evident in MCI patients, which could complicate the use of fMRI as an early detection component.…”
Section: Functional Mri (Fmri)mentioning
confidence: 95%
“…It has been found that AD patients have reduced activity in the MTL [117], particularly in the hippocampus [117][118][119][120][121], but also in the entorhinal cortex [117], while an increased activation has been reported in the prefrontal cortex, probably, due to a compensation mechanism [122,123]. Deactivation in posteromedial cortical areas such as the posterior cingulate and the medial parietal cortex has also been found to be anomalous in AD patients [124,125]. Nevertheless, these anomalies are much less evident in MCI patients, which could complicate the use of fMRI as an early detection component.…”
Section: Functional Mri (Fmri)mentioning
confidence: 95%
“…Most of the studies found that smaller hippocampal volumes, predominantly in the subicular and CA1 areas, are related to an increased risk for conversion from aMCI to AD [20][21][22][23][24] , despite some inconsistent findings [25,26] .…”
mentioning
confidence: 99%
“…The presence of the two older groups (second and the third) in our study, in which age was not significantly different but the number of lipofuscin-bearing neurons and CA were, might be explained as the consequence of different brain aging patterns [49]. Finally, such a metabolic state of the parahippocampal gyrus neurons can indirectly support Keller's [4] hypothesis that such senescence-related changes, like CA and lipofuscin deposits, might represent predecessors for more serious changes, like the ones observed in the early phase of AD in the entorhinal area as part of the parahippocampal region [5][6][7][8][9][10][11][12][13][14][15]. Future research should include the development of in vivo methods of CA and lipofuscin deposit detection and quantification in the brain of the elderly individuals.…”
mentioning
confidence: 61%
“…These findings, and the fact that in the early phases of AD the first pathological changes occur in the entorhinal cortex [5][6][7][8][9][10][11][12][13][14][15], stressed the importance of the histological findings, especially of MTL areas, that might improve the understanding of the cellular basis for the various degrees of cognitive decline within healthy elderly populations. Until recently it was generally believed that age-related impairments in cognitive performance are the result of age-related neuron loss, especially within the hippocampus and most neocortical areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation